Theoretical Study of Factory Machine Equipment: Manual vs Artificial Intelligent - Valentina Murni Sania; Gunawan, Cakti Indra (International Journal of Management and Business, 2024)
The development of industrial technology has brought significant changes in the factory operational system, especially in the use of machine tools. This study aims to describe the theoretical factory machine tools: manual vs AI and the theoretical factory machine tools manual vs AI. The research method uses triangulation comparative analysis. The results show that The study shows that the implementation of AI-based machines offers significant advantages over manual machines, especially in terms of efficiency, productivity, and predictive maintenance. Although AI implementation faces some challenges, such as initial costs and the need for skilled human resources, the long-term benefits are enormous for the industry.